1994
DOI: 10.1093/ajh/7.8.731
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Captopril and Nicardipine on Insulin Sensitivity and Thrombotic Profile in Patients With Hypertension and Android Obesity

Abstract: Hypertension is often related to metabolic disorders, such as android obesity, glucose intolerance, dyslipidemia, and hyperinsulinism (X syndrome). Insulin resistance (IR), described as the common link among these disorders, could contribute to an increase in coronary risk. The euglycemic insulin clamp technique has been used to show that different classes of antihypertensive agents have different effects on IR. The purpose of this multicenter study was to compare the effects of captopril to those of nicardipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…8,20,21 However, mean BMI at baseline in the present study (34.4 kg/m 2 ) was higher than in previous studies and suggests that close to half of the patients enrolled had BMI Ն35 kg/m 2 , that is, obesity grade 2 (BMI: 35 to 39.9 kg/m 2 ) or grade 3 (BMI: Ն40 kg/m 2 ). Nevertheless, BP control rates with aliskiren/ HCTZ compare favorably with the control rates of 34% and 38% observed with valsartan and the ␤-blocker atenolol, respectively (with addition of 12.5 to 25 mg of HCTZ as LSM indicates least-squares mean.…”
Section: Discussioncontrasting
confidence: 72%
“…8,20,21 However, mean BMI at baseline in the present study (34.4 kg/m 2 ) was higher than in previous studies and suggests that close to half of the patients enrolled had BMI Ն35 kg/m 2 , that is, obesity grade 2 (BMI: 35 to 39.9 kg/m 2 ) or grade 3 (BMI: Ն40 kg/m 2 ). Nevertheless, BP control rates with aliskiren/ HCTZ compare favorably with the control rates of 34% and 38% observed with valsartan and the ␤-blocker atenolol, respectively (with addition of 12.5 to 25 mg of HCTZ as LSM indicates least-squares mean.…”
Section: Discussioncontrasting
confidence: 72%
“…The beneficial effects of inhibition of the RAS in the progression of diabetic nephropathy, hypertension and cardiovascular diseases have been reported in many clinical trials (Shieh et al 1992, Torlone et al 1993, Raccah et al 1994, Mohanran & Toto 2003. Ang II has been found to attenuate or inhibit insulin signalling in vascular smooth muscle cells (Vellosa et al 1996, Folli et al 1997, Fukuda et al 2001, implicating a role for the RAS in regulating the actions of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,[34][35][36] Several experimental studies have shown that PAI-1 activity is stimulated by angiotensin II, or associated with ACE gene polymorphism, 37 although this latter association has been questioned by others. 38 Thus, antihypertensive drugs acting within the renin-angiotensin system should also exert effects within the fibrinolytic system.…”
Section: Discussionmentioning
confidence: 99%